Nanoimprint Lithography Enabling High-Performance Organic Optoelectronics: Advances and Perspectives - Song, Ningning; Guo, Xinghao; Zhao, Hongqiao; Li, Bohang; Liang, Ningning; Zhai, Tianrui (Nano-Micro Letters, 2026)
Organic optoelectronic devices demonstrate immense potential in flexible displays, wearable electronics, and artificial skin, needing precise light-field and morphology management strategies to further improve their opto-electric performance. Nanoimprint lithography (NIL) has emerged as a high-resolution, high-efficiency, and low-cost patterning technique that mechanically transferring micro/nanoscale patterns from a template to a substrate to significantly enhance the optoelectronic performance through the precise creation of advanced light-management structures, combined with additional solid-state stacking morphology. This review systematically summarizes recent advances in NIL technology for organic optoelectronics. It begins with an introduction to the fundamental principles, main process variants (thermal, ultraviolet, and electrochemical NIL), as well as key technical issues. Subsequently, through specific applications in organic light-emitting diodes, organic solar cells, and organic field-effect transistors, it highlights the exceptional capabilities of NIL to enhance device performance by controlling crystallization and creating functional micro/nanostructuring. Specific advantages include enabling high-efficiency light management to overcome efficiency bottlenecks, facilitating low-cost, high-throughput manufacturing for industrialization, full compatibility with flexible substrates for emerging applications, enabling multifunctional integration and novel device architectures, and tailoring material microstructures and properties advance fundamental research. Finally, we discuss the remaining challenges and future prospects of NIL in integrated organic optoelectronic systems. Highlights: 1 Nanoimprint lithography (NIL) enables high-performance light management in organic light-emitting diodes and organic solar cells, and enhances charge transport in organic field-effect transistors via controlled molecular ordering, pushing organic optoelectronics beyond conventional efficiency limits. 2 The technology provides a scalable, low-cost platform for large-area fabrication on flexible substrates, effectively bridging the gap between laboratory innovation and industrial mass production. 3 NIL uniquely empowers the creation of multifunctional integrated devices and novel architectures, opening pathways for next-generation wearable electronics and bio-integrated systems.